Characterisation of the effects of the food borne toxicant furan on Caenorhabditis elegans - Below, Cristina Catherine (2011)
Furan is a toxic organic compound which is usually used in industry where it helps in the production of nylon, lacquers, insecticides, or pharmaceuticals. But it has also been found in certain foods, mainly those that undergo heat treatment, such as tinned and jarred food including sauces, vegetables, and baby food (European Food Safety Authority, 2004; Jestoi et al., 2009; U.S. Food and Drug Administration, 2004). Furan has been shown to induce liver tumors and cholangiocarcinomas (Burka et al., 1991). As of 1995 furan is classified as "possibly carcinogenic to humans (Group 2B)" by the International Agency for Research on Cancer (IARC). However, the mechanisms of furan toxicity are still unknown. Studies have yielded different results as to whether or not it shows genotoxic activity. It is also suspected that the genotoxic effects shown by some studies were induced by the toxic metabolite cis-2-butene-1,4-dial (Burka et al., 1991; Peterson et al., 2006). Genotoxic carcinogens can cause cancer in very low doses, as even a single DNA adduct may lead to a mutation that causes cancer. For risk assessment purposes it is therefore highly important to know what mechanisms of action are involved in furan carcinogenesis. In this work I was trying to characterise the mechanisms of furan toxicity by identifying genes conferring furan resistance to previously generated C. elegans mutants. Furthermore, I looked at the visible effects of furan on C. elegans and the induction of genes known to be involved in stress response pathways. Frozen stocks of mutant worms were thawed and L4 larvae incubated in furan for four days. The number of offspring was then counted and compared to N2 wild type worms. Several changes had to be made to the original protocol, but furan resistance could not be confirmed for any of the frozen stocks. It was found that 90 mM furan kills adult worms so the following experiments were done with concentrations ranging from 0 to 80 mM furan. To further characterise the toxic effects of furan on C. elegans, GFP reporter strains were used to monitor gene induction following incubation in furan. Several genes were assayed, which are known to be involved in C. elegans stress response. In addition, the effects of furan on growth and feeding were investigated. None of the genes tested in the GFP reporter assay showed induction after exposure of C. elegans to furan. However, it could be shown that furan affects C. elegans feeding and growth. Since furan resistance could not be confirmed for any of the frozen stocks, SNP mapping and subsequent whole genome sequencing could not be done to identify the mutation. It could be shown that furan has an inhibitory effect on C. elegans feeding, egg laying, and growth. Feeding is inhibited in a dose-dependent manner with an EC50 of about 70 mM. C. elegans completely stop feeding at 80 mM. Similarly, egg laying is inhibited in a dose-dependent manner with an EC50 of about 20 mM. Growth seems to be affected by furan as well. However, these results could not be confirmed yet. Unfortunately, none of the genes tested in the GFP reporter assay was induced, so it was not possible to identify any proteins affected by furan toxicity.